The T1048I mutation in ATP7A gene causes an unusual Menkes disease presentation - León-García Gregorio; Santana Alfredo; Villegas-Sepúlveda Nicolás; Pérez-González Concepción; Henrríquez-Esquíroz José M; de León-García Carlota; Wong Carlos; Baeza Isabel (BMC, 2012)
Abstract Background The ATP7A gene encodes the ATP7A protein, which is a trans-Golgi network copper transporter expressed in the brain and other organs. Mutations in this gene cause disorders of copper metabolism, such as Menkes disease. Here we describe the novel and unusual mutation (p.T1048I) in the ATP7A gene of a child with Menkes disease. The mutation affects a conserved DKTGT1048 phosphorylation motif that is involved in the catalytic activity of ATP7A. We also describe the clinical course and the response to copper treatment in this patient. Case presentation An 11-month-old male Caucasian infant was studied because of hypotonia, ataxia and global developmental delay. The patient presented low levels of serum copper and ceruloplasmin, and was shown to be hemizygous for the p.T1048I mutation in ATP7A. The diagnosis was confirmed when the patient was 18 months old, and treatment with copper-histidinate (Cu-His) was started immediately. The patient showed some neurological improvement and he is currently 8 years old. Because the p.T1048I mutation affects its catalytic site, we expected a complete loss of functional ATP7A and a classical Menkes disease presentation. However, the clinical course of the patient was mild, and he responded to Cu-His treatment, which suggests that this mutation leads to partial conservation of the activity of ATP7A. Conclusion This case emphasizes the important correlation between genotype and phenotype in patients with Menkes disease. The prognosis in Menkes disease is associated with early detection, early initiation of treatment and with the preservation of some ATP7A activity, which is necessary for Cu-His treatment response. The description of this new mutation and the response of the patient to Cu-His treatment will contribute to the growing body of knowledge about treatment response in Menkes disease.